Assessing failure patterns of radical intent radiation strategies in patients with locally advanced carcinoma of the esophagus. Issue 3 (28th December 2020) - Mishra, Shagun; Ahmad, Farhan; Singh, Shalini; Singh, Rajneesh K.; Das, Koilpillai J. Maria; Kumar, Shaleen
Abstract: Background: Patterns of failure following definitive CRT (dCRT) are different as compared to neoadjuvant chemoradiotherapy (NACRT) with increased locoregional failures documented with dCRT. Aim: To document failure patterns in patients with esophageal carcinoma treated with neoadjuvant and definitive intent radiation strategies. Methods: Subjects were 123 patients treated with two chemoradiotherapy strategies. Group 1 (n = 99) underwent dose escalated definitive chemoradiotherapy (dCRT), Group 2 (n = 24) received neoadjuvant chemoradiotherapy (NACRT) followed by surgery. Cumulative incidence of locoregional failure (LRF), local failure (LF), regional lymph node failure (RLNF), and distant metastasis (DM) were computed; differences between the groups was evaluated using log rank test. Univariable and multivariable predictors of failure were identified using Cox regression analysis. Results: Cumulative LRF: 64% in Group 1 vs 35% in Group 2 ( P = .050). Cumulative LF: 59% in Group 1 vs 12% in Group 2 ( P = .000). Cumulative RLNF: 30% in Group 1 vs 24% in Group 2 ( P = .592). Most common RLNF: mediastinum for both groups (6% vs 12.5%, respectively). Distant metastasis: 40.4% Group 1 vs 17% Group 2 ( P = .129), predominantly lung (Group 1, 5%), and nonregional nodes (Group 2, 8.3%). Univariate analysis identified age ≤50, absence of concurrent chemotherapy, dose ≤50 Gy, and incomplete radiotherapy to predict higher odds of LRF and DM for Group 1; absence of comorbidities predicted for lower odds of LRF for Group 2. Age ≤50 predicted for higher odds of RNLR for Group 1, while absence of comorbidities predicted for lower odds of RNLR in Group 2. Multivariate analysis identified age ≤50, incomplete radiotherapy, and absence of concurrent chemotherapy to predict higher odds of LRF for Group 1. Age ≤50, absence of concurrent chemotherapy predicted higher odds of DM for Group 1. Absence of comorbidity predicted lower odds of LRF in Group 2. Conclusion: LRF is common in both groups, with LF being predominant in dCRT as opposed to RNLF in NACRT. Age ≤50, absence of concurrent chemotherapy is a predictor of LRF and DM in dCRT.